Kirigami-inspired deployable mechanisms with a type-preserving feature and controllable Poisson’s ratio - Wang, Jianzhi; Xiao, Hang; Ding, Xilun; Lyu, Shengnan (Frontiers in Mechanical Engineering, 2023)
The spatial deployable mechanism is capable of adapting to different operating requirements by adjusting its shape and size. However, most current deployable mechanisms fail to maintain the type of their reflective surface during the folding process, which limits their ability to adjust the optimal operating frequency. To address this issue, this paper presents a novel design of a deployable mechanism with a type preserving feature inspired by kirigami techniques. By preserving the type of its reflective surface, this mechanism allows for the adjustment of the optimum operating frequency according to specific requirements. This makes it well-suited for deployment on commercial satellites that undergo constant mission variations. The mechanism is constructed using porous kirigami cells, ensuring that the type of the working surface is maintained throughout the deployment process. The construction of deployable units and networks based on porous cells is also discussed. Additionally, deployable mechanisms with controllable Poisson's ratios are developed. The kinematics of the mechanism are analyzed to verify the type-preserving characteristics. Finally, four case studies are conducted to illustrate and validate the proposed design and analysis. This is a provisional file, not the final typeset article Kirigami is a combination of paper cutting and folding. It can obtain a three-dimensional structure with a certain functional type from a compact storage (flat) configuration. Kirigami can effectively provide new ideas and solutions for the design of deployable mechanisms. Saito et al. proposed a novel method to construct arbitrary cross-section composite honeycombs by changing the crease and cut pattern 9,10 . Broccolo et al. described the development, manufacturing and testing of a zero Poisson's ratio cellular structure using kirigami-inspired techniques 11 . Calisch et al. designed an algorithm for producing a processable cut-and-fold pattern from a three-dimensional volume 12 . Neville et al. presented a shape memory polymer honeycomb with tuneable and shape morphing mechanical characteristics 13 . Lyu et al. developed a novel family of cellular mechanical metamaterials based on rigid-foldable square-twist origami 14 .